Workplace Competence and Discipline's Effects on Career Development and Performance - Marayasa, I Nyoman (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
It is hoped that the performance of the National Police in providing protection, protection and community service from day to day will continue to be improved. Career development is urgently needed by members of the Denpasar Police to be more motivated to work optimally. With this aim in this study to analyze competence, work discipline, career development and performance. To answer the above objectives, a descriptive method with a quantitative approach is needed, with a sample of 214 respondents, the sampling method used is probability sampling. This study uses a linear regression analysis design, validity test and classical assumption test. The results of this study show that there is a positive and significant influence between competence on performance, work discipline on performance, and career development on performance.